Formation of polymer microcapsules with encapsulated Fe3O4 magnetic nanoparticles - Melnyk, Roman; Serdiuk, Vitalii; Kovalenko, Tetiana (Lviv Polytechnic Publishing House, 2015)
Surface functionalized iron oxide magnetic nanoparticles (MNPs) are a kind of novel functional materials, which can be widely used in biotechnology and catalysis as magnetic separation systems. Therefore the goal of our work was to study preparation of encapsulated MNPs by elaborated extraction-coacervation technique using synthesized heterofunctional acrylate copolymer. Magnetite MNPs modified by oleic acid were synthesized and used in encapsulation process. Developed encapsulation technique allowed to obtain microcapsules with Fe3O4 nanoparticles encapsulated in paraffin core possessing magnetic properties and covered by heterofuntional copolymer shell.
Keywords: heterofunctional acrylate copolymer; magnetite; magnetic nanoparticles; encapsulation; microcapsules